Analysis of Application Based on Cloud Computing in Banking Industries in Indonesia Using Technology Acceptance Model (TAM) 2 Method Case Study The National Private Banks in Surabaya and Bali Region - I Wayan Jatu Wira Purnama; Raden Venantius Hari Ginardi (Institut Teknologi Sepuluh Nopember, 2019)
Cloud computing applications remain rarely used in the banking industry in Indonesia. X is one of the national private banks in Indonesia, which is the first bank to use cloud computing application in their operations. Since it is the first bank to use such technology, the the researcher aims to measure the acceptance and ease of use of cloud computing-based applications, and to measure the level of user satisfaction with the TAM 2 method (Technology Acceptance Model 2). The researcher used the TAM 2 method because it is the development of the TAM 1 method which adds social influence and external perspective variables. Variables in TAM 2 are subjective norms, image, result demonstrability, job relevance, voluntariness, perceived usefulness, perceived ease of use, intention to use and usage behavior. Distribution of questionnaire samples was conducted to 90 respondents in Surabaya and Bali. Data from the questionnaire were tested in terms of validity and reliability, correlation and regression, variable descriptive analysis, and hypothesis. From the results, it was found that the twelve hypotheses in TAM 2 were all acceptable and the most significant effect was the outcome quality variable towards the benefits of using cloud computing applications at 41.2%. Therefore, it can be concluded that the greater the quality of the result of cloud computing applications, the greater the benefits of the technology